MANTA versus ProGlide vascular closure devices in transfemoral transcatheter aortic valve implantation - Fausto Biancari; Hannu Romppanen; Mikko Savontaus; Antti Siljander; Timo Mäkikallio; Olli-Pekka Piira; Jarkko Piuhola; Viivi Vilkki; Antti Ylitalo; Tuija Vasankari; Juhani K.E. Airaksinen; Matti Niemelä (ELSEVIER IRELAND LTD, 2022)
Background: The MANTA system is a novel vascular closure device (VCD) and its safety and efficacy were compared to the ProGlide VCD in patients undergoing transfemoral transcatheter aortic valve implantation (TAVI).
Methods: This is a retrospective study including 222 patients who underwent transfemoral TAVI at three Finnish University Hospitals. The MANTA VCD was used in 107 patients and their outcome was compared with that of 115 patients in whom the arterial access was closed with the ProGlide VCD.
Results: VARC-2 VCD failure occurred less frequently in the MANTA cohort (3.7% vs. 7.8%, p = 0378), but the difference did not reach statistical significance. When adjusted for the introducer outer diameter, the MANTA cohort had similar rates of VARC-2 major vascular complications (93% vs. 12.2%, adjusted: p = 0.456), VARC-2 life-threatening/disabling bleeding (93% vs. 6.1%, adjusted: p = 0.296) and need of invasive treatment of bleeding (4.7% vs. 7.0%, adjusted: p = 0.416) compared to the ProGlide cohort. Additional VCDs were more frequently needed in the ProGlide cohort (583% vs. 1.9%, p < 0.0001).
Conclusions: In patients undergoing transfemoral TAVI, the MANTA VCD showed a similar risk of VARC-2 vascular and bleeding complications compared to the ProGlide VCD, but it reduced significantly the need of additional VCDs for completion of hemostasis.